2014
DOI: 10.1254/jphs.13252fp
|View full text |Cite
|
Sign up to set email alerts
|

Butea superba–Induced Amelioration of Cognitive and Emotional Deficits in Olfactory Bulbectomized Mice and Putative Mechanisms Underlying Its Actions

Abstract: Abstract. This study investigated the effects of alcoholic extract of Butea superba (BS) on cognitive deficits and depression-related behavior using olfactory bulbectomized (OBX) mice and the underlying molecular mechanisms of its actions. OBX mice were treated daily with BS (100 and 300 mg/kg, p.o.) or reference drugs, tacrine (2.5 mg/kg, i.p.) and imipramine (10 mg/kg, i.p.) from day 3 after OBX. OBX impaired non-spatial and spatial cognitive performances, which were elucidated by the novel object recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Employing a modified version of the Y-maze test and a novel ORT (Han et al, 2008;Sithisarn et al, 2013;Yamada et al, 2011;Zhao et al, 2007), we subsequently elucidated the effects of TLL on short-term spatial and non-spatial working memory performance of OBX animals, respectively. In agreement with our previous reports (Mizuki et al, 2014;Sithisarn et al, 2013;Yamada et al, 2011), OBX clearly impaired spatial and non-spatial working memory performance in the modified Y-maze test and novel ORT in a manner reversible by the daily administration of tacrine, supporting the concept that facilitation of the central cholinergic function is beneficial for improving hippocampus-dependent spatial memory deficits and hippocampus-independent non-spatial memory deficits of OBX animals. Moreover, the present study demonstrated that although the daily administration of TLL tended to improve OBX-induced spatial working memory deficits in the modified Y-maze test, the same treatment as well as tacrine administration significantly ameliorated OBX-induced non-spatial working memory deficits identified in the novel ORT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Employing a modified version of the Y-maze test and a novel ORT (Han et al, 2008;Sithisarn et al, 2013;Yamada et al, 2011;Zhao et al, 2007), we subsequently elucidated the effects of TLL on short-term spatial and non-spatial working memory performance of OBX animals, respectively. In agreement with our previous reports (Mizuki et al, 2014;Sithisarn et al, 2013;Yamada et al, 2011), OBX clearly impaired spatial and non-spatial working memory performance in the modified Y-maze test and novel ORT in a manner reversible by the daily administration of tacrine, supporting the concept that facilitation of the central cholinergic function is beneficial for improving hippocampus-dependent spatial memory deficits and hippocampus-independent non-spatial memory deficits of OBX animals. Moreover, the present study demonstrated that although the daily administration of TLL tended to improve OBX-induced spatial working memory deficits in the modified Y-maze test, the same treatment as well as tacrine administration significantly ameliorated OBX-induced non-spatial working memory deficits identified in the novel ORT.…”
Section: Discussionsupporting
confidence: 92%
“…After completing the behavioral experiments, mice were decapitated and the frontal cortices were dissected out and kept at À80 C until use. Determination of cholinesterase activity was performed on the basis of the colorimetric method by slightly modifying previous methods (Ellman et al, 1961;Mizuki et al, 2014;Zhao et al, 2007). Briefly, the frozen cortex was weighed and homogenized in 10 volumes of 0.1 M phosphate buffer (pH 7.4) containing 1% Triton X-100.…”
Section: Ex Vivo Measurement Of Cholinesterase Activity In the Brainmentioning
confidence: 99%
“…Mice were placed in the testing room for 1 h prior to the behavioral test for habituation. The order of the behavioral tests was as follow: Y-maze test (day 45), FST (pre-swimming on day 47-48, test session on day [48][49], and TST (day 51-52). One day after completion of the behavioral tests, the mice were decapitated.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…The arms were positioned at equal angles, in a Y-shape. One hour after drug administration, the mice were individually placed on one arm, and the total arm entries were recorded manually, over an 8 min period, for measuring the locomotion activity [48].…”
Section: Locomotor Testmentioning
confidence: 99%
“… 20 These studies raise the possibility that novel agents effective for psychological disorders may be found from the traditional herbal remedies. We also have reported that several traditional herbal medicines or medicinal herbs, such as Butea superba , 21 , 22 Bacopa monnieri 23 and Chotosan (鉤藤散gōu téng sǎn), 24 ameliorate cognitive and emotional deficits in several types of model mice. Sansoninto (SST; 酸棗仁湯 suān zǎo rén tāng) is a traditional herbal medicine that has been used in China, Taiwan, and Japan for adult patients with insomnia, depression, and neuropathy.…”
Section: Introductionmentioning
confidence: 97%